The Impact Of Covid-19 On Islamic Banking In Indonesia During The Pandemic Era (Journal of Entrepreneurship and Business, 2020)
The impact of COVID-19 on Islamic banking can be analysed into three possible risks, such as financing risks, impairment of assets, and tightening the profit-sharing system. Compared to conventional banks, Islamic banking is more flexible in meeting the economic crisis caused by the COVID-19 pandemic. Basically, the national banking system had predicted trouble due to the COVID-19 epidemic. On the other hand, Islamic banks are at an advantage with the theory of profit-sharing, thus increasing its effectiveness in dealing with crises. Islamic banks’ dominance throughout these challenging times is undoubtedly an excellent opportunity to strengthen their market share. Besides, Islamic banks can face risks, such as providing loans, deteriorating asset quality, and tightening profit sharing. Therefore, Islamic banks must understand these risks to ensure their plans during the COVID-19 pandemic. Admittedly, performing restricted expansion into the digital share is a challenging decision that should be practised by Islamic banks. In view of the recent pandemic, this study aimed to analyse the three risks faced by Islamic banking in Indonesia.
Keywords: Array; Array; Array; Array; Array